4/5 x 1 1/6 =

Question

Asked 3/1/2013 9:08:07 AM

Updated 8/14/2014 5:57:46 AM

2 Answers/Comments

This conversation has been flagged as incorrect.

Edited by jeifunk [8/14/2014 5:57:46 AM]

Rating

3

4/5 * 1 1/6

= 4/5 * 7/6;

= 28/30;

= 14/15

= 4/5 * 7/6;

= 28/30;

= 14/15

Added 8/13/2014 1:23:17 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [8/13/2014 1:41:37 PM]

3

(-17) - (-22) = -17 + 22 = 5

Added 8/13/2014 1:23:40 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [8/13/2014 1:41:57 PM]

4/5 x 1 1/6 **Weegy:** x+(4)/(x)+2=x+(1)/(x)+5
To add fractions, the denominators must be equal. The denominators can be made equal by finding the least common denominator (LCD). In this case, the LCD is x. [ Next, multiply each fraction by a factor of 1 that will create the LCD in each of the fractions.
x+(4)/(x)+2=x*(x)/(x)+(1)/(x)+5*(x)/(x)
Multiply x by x to get x^(2).
x+(4)/(x)+2=(x^(2))/(x)+(1)/(x)+5*(x)/(x)
Multiply 5 by x to get 5x.
x+(4)/(x)+2=(x^(2))/(x)+(1)/(x)+(5x)/(x)
Combine the numerators of all expressions that have common denominators.
x+(4)/(x)+2=(x^(2)+1+5x)/(x)
Reorder the polynomial x^(2)+1+5x alphabetically from left to right, starting with the highest order term.
x+(4)/(x)+2=(x^(2)+5x+1)/(x)
Find the LCD (least common denominator) of x+(4)/(x)+2+((x^(2)+5x+1))/(x).
Least common denominator: x
Multiply each term in the equation by x in order to remove all the denominators from the equation.
x*x+(4)/(x)*x+2*x=(x^(2)+5x+1)/(x)*x
Cancel the common factor of x in the denominator of the first term (4)/(x) and the second term x.
x*x+(4)/( x )* x +2*x=(x^(2)+5x+1)/(x)*x
Reduce the expression by removing the common factor of x in the denominator of the first term (4)/(x) and the second term x.
x*x+4*1+2*x=(x^(2)+5x+1)/(x)*x
Multiply x by x to get x^(2).
x^(2)+4*1+2*x=(x^(2)+5x+1)/(x)*x
Multiply 4 by 1 to get 4.
x^(2)+4+2*x=(x^(2)+5x+1)/(x)*x
Multiply 2 by x to get 2x.
x^(2)+4+2x=(x^(2)+5x+1)/(x)*x
Reorder the polynomial x^(2)+4+2x alphabetically from left to right, starting with the highest order term.
x^(2)+2x+4=(x^(2)+5x+1)/(x)*x
Cancel the common factor of x from the denominator of the first expression and the numerator of the second expression.
x^(2)+2x+4=(x^(2)+5x+1)/( x )* x
Cancel the common factor of x from the denominator of the first expression and the numerator of the second expression.
x^(2)+2x+4=(x^(2)+5x+1)
Remove the parentheses around the expression x^(2)+5x+1.
x^(2)+2x+4=x^(2)+5x+1
Since x^(2) contains the variable to solve for, ... (More)

Question

Expert Answered

Updated 6/12/2014 5:13:13 PM

1 Answer/Comment

27,352,279

questions answered

There are no comments.